Genome-wide identification and expression analysis of the glutamate receptor gene family in sweet potato and its two diploid relatives - Hu, Yaya; Dai, Zhuoru; Huang, Jinan; Han, Meikun; Wang, Zhiwei; Jiao, Weijing; Gao, Zhiyuan; Liu, Xinliang; Liu, Lanfu; Ma, Zhimin (Frontiers in Plant Science, 2023)
Plant glutamate receptor (GLR) homologs are crucial calcium channels that play an important role in plant development, signal transduction, and response to biotic and abiotic stresses. However, the GLR gene family has not yet been thoroughly and systematically studied in sweet potato. In this study, a total of 37 GLR genes were identified in the cultivated hexaploid sweet potato (Ipomoea batatas), and 32 GLR genes were discovered in each of the two diploid relatives (Ipomoea trifida and Ipomoea triloba) for the first time. Based on their evolutionary relationships to those of Arabidopsis, these GLRs were split into five subgroups. We then conducted comprehensive analysis to explore their physiological properties, protein interaction networks, promoter cis-elements, chromosomal placement, gene structure, and expression patterns. The results indicate that the homologous GLRs of the cultivated hexaploid sweet potato and its two relatives are different. These variations are reflected in their functions related to plant growth, hormonal crosstalk, development of tuberous roots, resistance to root rot, and responses to abiotic stress factors, all of which are governed by specific individual GLR genes. This study offers a comprehensive analysis of GLR genes in sweet potato and its two diploid relatives. It also provides a theoretical basis for future research into their regulatory mechanisms, significantly influencing the field of molecular breeding in sweet potatoes.